Analysis of Factors Affecting Welfare of Pepper Farmers in Inebenggi Village Mowewe District East Kolaka Regency - Pama'tan, Aska; Rianse, Ilma Sarimustaqiyma; Hidrawati, Hidrawati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Well-being farmers could be influenced by multiple factors well-being large land, education, and total dependents, with level well-being farmer determined by ratio expenditure food and non -food House stairs. Study this aim for knowing well-being farmer pepper and influencing factors - well-being farmer pepper in the village Inebenggi districts Mowewe East, County Kolaka. Study this done on September - October 2021. The population in a study is 23 houses stairs, with use method census acquired 23 houses ladder as sample research. Variable in a study is identity respondents, welfare, and influencing factors - welfare. Data analysis for well-being using the Good Service Ratio and theory poverty and descriptive quantitative research through the equation model regression multinomial logistics. Results study show that well-being farmer in the village Inebenggi with using the Good Service Ratio states farmer not prosperous enough, while theory poverty state farmer successful and factor significant influence - well-being farmer is large land. And education